Emoção na educação infantil: um olhar sobre a aprendizagem na convivência humana - Silva, Rafaela da Rocha (2018)
The school is a social institution that is present since the beginning of life and that constitutes a source of social interactions in which emotions are present, providing a filler learning process of different human aspects. This way, realizing the importance of emotions in the childish educational context to development and learning of children from 0 to 5 years old and highlighting the social aspect of learning, the main goal of this work is to clarify how Childhood Education teachers conceive emotion in the educational process. This unfolds in the following specific goals: investigate how teachers of Childhood Education deal with their emotions in their teaching; observe how they mediate the emotions in the social dynamic established in the classroom; comprehend how they relate emotion and education. To reach these research goals, interviews were made with teachers of Childhood Education of a particular school in São Luís, Maranhão. Their speech is refered in the work through fictitious names and was analyzed under the theorical referential light built and presented in the initial chapters. The analyses were made taking into consideration three basic pillars: the goals of the research, the conceptual structure presented in the work and the social reality in which participants and researcher are immersed. The contents were organized, classified and analyzed according to analysis axis and each category is composed by tangles between common aspects, observed in the participants’ speeches, and the theorical sustenance, enabling the reader to comprehend the construction processes of new knowledges from qualitative analysis. In this regard, the obtained results were the following: the teachers deal with their emotions perceiving them in the school context, preventing them to damage the educational process; they manage emotions providing to students a cozy environment, founded in lovingness and care; they affirm that emotion and learning are intimately connected, being the first facilitator or blocker of the second, depending on how human coexistence is structured in the classroom.